Automobile essence for removing formaldehyde and releasing negative ions and preparation method thereof

By combining modified electrical powder, nano-titanium oxide core-shell particles, and sodium alginate network structure, the problem of poor formaldehyde removal and negative ion release effects in existing automotive essences has been solved, improving the product's antibacterial properties and negative ion release capabilities.

CN121103056AActive Publication Date: 2025-12-12YUANYANGXING (CHONGQING) HEALTH TECHNOLOGY CO LTD

Patent Information

Application Number
CN202511667001.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-14
Publication Date
2025-12-12
Estimated Expiration
2045-11-14

AI Technical Summary

Technical Problem

Existing car serums are not effective in removing formaldehyde and releasing negative ions, and their antibacterial effects are insufficient to meet market demand.

Method used

The combination of negative ion release enhancement component and formaldehyde removal component is adopted. The negative ion release enhancement component forms core-shell particles through modified electrical powder and nano titanium dioxide structure, while the formaldehyde removal component forms a three-dimensional network structure through materials such as sodium alginate and allyl glycidyl ether, which enhances the ability to adsorb and decompose formaldehyde.

Benefits of technology

It significantly improves the formaldehyde removal performance, negative ion release capacity, and antibacterial effect of car essence, achieving more efficient formaldehyde removal and negative ion release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of automobile essence preparation, and particularly discloses automobile essence capable of removing formaldehyde and releasing anions and a preparation method of the automobile essence. Comprising the following raw materials in parts by weight: 500-600 parts of deionized water, 18-24 parts of a negative ion release enhancing component, 12-20 parts of an aldehyde removing component, 30-40 parts of absolute ethyl alcohol, 8-14 parts of a dispersing agent, 14-18 parts of phenoxyethanol, 22-26 parts of an initiator solution and 6-10 parts of citral. A negative ion release enhancing component and a formaldehyde removal component are added, the negative ion release enhancing component is prepared by modifying core-shell particles with a silane coupling agent, the outer layer of each core-shell particle is of a porous titanium dioxide structure, the inner core of each core-shell particle is modified electrical powder, and the formaldehyde removal component is prepared by carrying out a ring-opening esterification reaction on sodium alginate and allyl glycidyl ether, so that the formaldehyde removal effect is improved. And then carrying out chemical cross-linking with hydroxypropyl acrylate and methacrylic acid, thereby coordinating and enhancing the formaldehyde removal capability, the anion release capability and the antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of automotive essence preparation technology, and more specifically, it relates to an automotive essence that removes formaldehyde and releases negative ions, and a method for preparing the same. Background Technology

[0002] As a car care product, car essence can not only effectively clean dirt from the car's surface and interior, but also provide comprehensive maintenance and protection for the car, and has a wide range of applications in the field of car beauty and maintenance.

[0003] Since most adhesives, paints, and plastic parts used in automotive interior trim materials use formaldehyde as a solvent or additive, they release pollutants, primarily formaldehyde, over time, posing a health risk. With increasing health awareness, providing a car essence that removes formaldehyde and releases negative ions has become particularly important.

[0004] Patent application 202011011529.5 discloses an automotive essence that removes formaldehyde and releases negative ions, and its preparation method. The raw materials, by weight, are: 800-1000 parts distilled water, 60-80 parts nano-sized seashell powder, 8-10 parts natural hydrosol extract, 30-40 parts negative ion powder, 40-60 parts titanate, 30-40 parts ethanol, 60-80 parts formaldehyde removal additive, 8-14 parts stabilizing dispersant, and 4-8 parts phenoxyethanol. The automotive essence prepared by this patent application has a good formaldehyde-removing effect, purifies the air inside the car, removes odors, and releases negative ions, which is beneficial to human health. However, the application simply mixes functionalized core-shell particles such as activated carbon powder, nano-titanium dioxide, and nano-silica in the preparation of the formaldehyde removal additive. These functionalized core-shell particles are prone to agglomeration, resulting in the prepared automotive essence having only average formaldehyde removal performance, negative ion release capacity, and antibacterial properties, which is difficult to meet market demands.

[0005] Based on the above-mentioned shortcomings, this application provides an automotive essence with excellent antibacterial effect that removes formaldehyde and releases negative ions, and its preparation method. Summary of the Invention

[0006] To address the problems mentioned in the background section, this application provides an automotive essence that removes formaldehyde and releases negative ions, and a method for preparing the same.

[0007] A car essence that removes formaldehyde and releases negative ions comprises the following raw materials in parts by weight: 500-600 parts deionized water, 18-24 parts negative ion release enhancing component, 12-20 parts formaldehyde removal component, 30-40 parts anhydrous ethanol, 8-14 parts dispersant, 14-18 parts phenoxyethanol, 22-26 parts initiator solution, and 6-10 parts citral. The preparation method of this car essence that removes formaldehyde and releases negative ions includes the following steps: Add the formaldehyde-removing component and anhydrous ethanol to deionized water and stir until homogeneous. While stirring, add the negative ion release enhancement component, dispersant, phenoxyethanol and initiator solution, heat to 76-80℃, continue stirring for 2-4 hours, cool to room temperature, then add citral and stir until homogeneous to obtain a car essence that removes formaldehyde and releases negative ions.

[0008] Preferably, the dispersant is Orotan 731A or BYK-190.

[0009] Preferably, the initiator solution is an aqueous solution of ammonium persulfate with a mass fraction of 12-16%.

[0010] Preferably, the negative ion release-enhancing component is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 8-9, stir until homogeneous, add dopamine, stir and react for 18-22 hours, filter, wash and dry to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.2-1.6:50-60:0.8-1.4. In the above reaction process, the phenolic hydroxyl structure contained in dopamine has good adhesion, and dopamine can self-polymerize in Tris-HCl buffer solution to form a polydopamine layer on the surface of electrical powder, giving the electrical powder excellent adhesion. Step A2: Add the pretreated electroplating powder, cerium nitrate, lanthanum nitrate, and zinc nitrate to deionized water, ultrasonically disperse until uniform, add 4-6M ammonia to adjust the pH to 8-9, stir for 25-35 minutes, filter, dry, and calcine at 430-460℃ for 24-28 minutes. Cool to room temperature to obtain modified electroplating powder. The mass ratio of pretreated electroplating powder, cerium nitrate, lanthanum nitrate, zinc nitrate, and deionized water is 4.5-5.5:0.65-0.85:0.6-0. .8:0.4-0.5:20-40, the polydopamine layer on the surface of the pretreated electrical powder has good adhesion and can adsorb cerium nitrate, lanthanum nitrate and zinc nitrate onto the surface of the pretreated electrical powder. Ammonia water, as a precipitant, can combine with cerium, lanthanum and zinc ions in cerium nitrate, lanthanum nitrate and zinc nitrate to form hydroxides. Through calcination, the hydroxide precipitates and pyrolyzes to form cerium oxide, lanthanum oxide and zinc oxide, thus realizing the formation of nano-cerium oxide, nano-lanthanum oxide and nano-zinc oxide on the surface of the pretreated electrical powder; Step A3: Mix the modified electrical powder and crosslinking agent evenly, adjust the pH to 2-2.2, then add tetrabutyl titanate, stir and dropwise add a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol and anhydrous ethanol, controlling the dropwise addition to be completed within 10 minutes. After the dropwise addition is complete, raise the temperature to 128-134℃ and continue stirring for 24-28 hours. Wash, dry, and then calcine at 490-510℃ for 2-2.2 hours to obtain functionalized core-shell particles. Mix the functionalized core-shell particles, deionized water, anhydrous ethanol and silane coupling agent evenly, raise the temperature to 40-46℃, stir for 6-8 hours, centrifuge, precipitate, wash and dry to obtain the negative ion release enhancing component. The mass ratio of modified electrical powder, crosslinking agent, tetrabutyl titanate and mixture a is 1.4-1. In the mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol, and anhydrous ethanol is 1:10-12:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol, and silane coupling agent is 2-4:10-16:32-40:1-1.4. In the above reaction process, polyvinyl alcohol is used as a pore-forming agent, polyoxyethylene polyoxypropylene ether is used as a dispersant, and the hydroxyl groups generated by the hydrolysis of tetrabutyl titanate can form hydrogen bonds with the hydroxyl groups in the crosslinking agent, thereby coating the modified electrical powder inside, and preparing core-shell particles with modified electrical powder as the inner layer and porous titanium dioxide structure as the outer shell. Then, the core-shell particles are treated with silane coupling agent to obtain the negative ion release enhancement component.

[0011] Preferably, the silane coupling agent is KH-550 or KH-540.

[0012] Preferably, in step A3, the crosslinking agent is a chitosan aqueous solution with a mass fraction of 1-3%.

[0013] Preferably, in step A3, the polyvinyl alcohol is polyvinyl alcohol 1000.

[0014] Preferably, the formaldehyde-removing component is prepared by the following steps: Step B1: Mix sodium alginate and deionized water, stir evenly at room temperature, adjust the pH to 10-11, then add allyl glycidyl ether dropwise, controlling the addition to be completed within 10 minutes, raise the temperature to 64-70℃, continue stirring for 5.4-6.2 hours, then adjust the pH to neutral, wash, and dry to obtain unsaturated sodium alginate. The mass ratio of sodium alginate, deionized water, and allyl glycidyl ether is 3.2-4.4:70-80:15. Under alkaline conditions, the carboxyl groups on sodium alginate and the epoxy groups on allyl glycidyl ether undergo a ring-opening esterification reaction to obtain unsaturated sodium alginate. Step B2: Add hydroxypropyl acrylate and methacrylic acid to deionized water, mix thoroughly, adjust the pH to 6-6.6, heat to 56-62℃, stir and dropwise add a mixture of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether, and anhydrous THF, controlling the addition to be completed within 15 minutes, continue stirring and reacting for 1.2-1.6 hours, wash, dry, and obtain the aldehyde-removing component, wherein hydroxypropyl acrylate, methacrylic acid, deionized water, and a mixture of... The mass ratio of liquid b is 1.2-1.6:40-50:20-28:0.06-0.08. In mixed liquid b, the mass ratio of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether, and anhydrous THF is 2.6-3.2:14-18:0.6-0.8:0.2-0.4:25. During the above reaction process, calcium ions in the saturated calcium chloride aqueous solution can chemically cross-link with sodium alginate, and at the same time, aldehyde-removing components are obtained.

[0015] Compared with the prior art, the present invention has the following beneficial effects: To improve the formaldehyde removal performance, negative ion release capacity, and antibacterial effect of the prepared automotive essence, this application takes a two-pronged approach. Firstly, a negative ion release enhancement component is added. This component is prepared by modifying core-shell particles with a silane coupling agent. The outer layer of the core-shell particles is a porous titanium dioxide structure, and the core is modified tourmaline powder. The presence of the porous titanium dioxide structure not only provides an extremely high specific surface area, effectively adsorbing formaldehyde, but also leverages the photocatalytic performance of nano-titanium dioxide, exhibiting excellent antibacterial properties and decomposing formaldehyde generated inside the car. Secondly, the hydroxyl radicals generated by titanium dioxide can undergo a chain reaction with the negative oxygen ions on the tourmaline surface, generating more negative ions. The modified tourmaline powder is doped with cerium ions, lanthanum ions, and zinc ions. The process yielded several advantages. Firstly, co-doping not only extends the light absorption range of tourmaline to the visible light region, enhancing its photocatalytic decomposition of organic matter and indirectly generating more negative ions, but also refines the crystal grains, improving the negative ion release efficiency of the car essence. Secondly, a formaldehyde-removing component was added. On one hand, the sodium alginate in the formaldehyde-removing component contains abundant carboxyl and hydroxyl groups, enabling it to form hydrogen bonds with formaldehyde molecules. On the other hand, the allyl glycidyl ether grafted onto the surface of the formaldehyde-removing component can form a three-dimensional network structure with hydroxypropyl acrylate and methacrylic acid, not only improving its formaldehyde removal capacity but also effectively fixing the high surface area activated carbon. Introducing it into the car essence allows it to work synergistically with the negative ion release-enhancing component, enhancing its formaldehyde removal capacity, negative ion release capacity, and antibacterial effect. Detailed Implementation

[0016] To make the implementation methods of this application easier to understand, the application will be described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not limited to the application scope of this application.

[0017] The main raw materials and their component contents used in the examples and comparative examples are shown below: Polyvinyl alcohol 1000 is commercially available from Shandong Xuanhao Environmental Protection Technology Co., Ltd., activated carbon is produced by Tianjin Jindong Tianzheng Fine Chemical Reagent Factory, electrolytic powder is 3000 mesh calcium carbide powder commercially available from Lingshou County Marble Mineral Products Processing Plant, and sodium alginate is commercially available from Anhui Lin'an Biotechnology Co., Ltd.

[0018] The present application will be further described in detail below with reference to embodiments and comparative examples.

[0019] Preparation Examples 1-3 and Comparative Preparation Examples 1-3 provide methods for preparing functionalized core-shell particles.

[0020] Preparation Example 1 This preparation example provides a negative ion release enhancement component, which is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 8, stir at 510 rpm for 12 min until homogeneous, add dopamine, maintain the stirring speed, and continue stirring for 18 h. Filter, wash three times with deionized water, and dry at 52 °C to constant weight to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.2:50:0.8. Step A2: Add the pretreated electrical powder, cerium nitrate, lanthanum nitrate, and zinc nitrate to deionized water. Control the ultrasonic frequency at 40kHz and the ultrasonic power at 600W, and sonicate for 14 minutes until homogeneous. While stirring at 460rpm, add 4M ammonia water to adjust the pH to 8, stir for 25 minutes, filter, dry at 46℃ to constant weight, calcine at 430℃ for 24 minutes, and cool to room temperature to obtain modified electrical powder. The mass ratio of pretreated electrical powder, cerium nitrate, lanthanum nitrate, zinc nitrate, and deionized water is 4.5:0.65:0.6:0.4:20. Step A3: The modified electrical powder and a 1% (w / w) chitosan aqueous solution are stirred at 480 rpm for 16 min until homogeneous. The pH is adjusted to 2 with an 18% (w / w) acetic acid solution. Tetrabutyl titanate is then added, and a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol (a) is added dropwise over 10 min. After the addition is complete, the temperature is raised to 128℃, and the stirring speed is maintained. The reaction is continued for 24 h. The mixture is washed three times each with anhydrous ethanol and deionized water, dried at 56℃ to constant weight, and then calcined at 490℃ for 2 h to obtain functionalized core-shell particles. The functionalized core-shell particles, deionized water, and... Anhydrous ethanol and KH-550 were stirred at 620 rpm for 14 min until homogeneous. The mixture was then heated to 40 °C and stirred for 6 h. After centrifugation, the precipitate was washed three times each with anhydrous ethanol and deionized water, and dried at 46 °C to constant weight to obtain the negative ion release enhancement component. The mass ratio of modified electrical powder, chitosan aqueous solution, tetrabutyl titanate, and mixture a was 1.4:40:3.2:20. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol was 1:10:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol, and KH-550 was 2:10:32:1.

[0021] Preparation Example 2 This preparation example provides a negative ion release enhancement component, which is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 8.5, stir at 530 rpm for 16 min until homogeneous, add dopamine, maintain the stirring speed, and continue stirring for 20 h. After filtration, wash four times with deionized water, and dry at 54 °C to constant weight to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.4:55:1.1. Step A2: Add the pretreated electrical powder, cerium nitrate, lanthanum nitrate, and zinc nitrate to deionized water. Control the ultrasonic frequency at 35 kHz and the ultrasonic power at 550 W, and sonicate for 18 min until homogeneous. While stirring at 500 rpm, add 5 M ammonia water to adjust the pH to 8.5. Stir for 30 min, filter, dry at 50°C to constant weight, calcine at 445°C for 26 min, and cool to room temperature to obtain modified electrical powder. The mass ratio of pretreated electrical powder, cerium nitrate, lanthanum nitrate, zinc nitrate, and deionized water is 5:0.75:0.7:0.45:30. Step A3: The modified electrical powder and a 2% (w / w) chitosan aqueous solution are stirred at 500 rpm for 20 min until homogeneous. The pH is adjusted to 2.1 with a 20% (w / w) acetic acid solution. Tetrabutyl titanate is then added, and a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol (a) is added dropwise over 10 min. After the addition is complete, the temperature is raised to 131℃, and the stirring speed is maintained. The reaction is continued for 26 h. The mixture is washed four times each with anhydrous ethanol and deionized water, dried at 60℃ to constant weight, and then calcined at 500℃ for 2.1 h to obtain functionalized core-shell particles. The functionalized core-shell particles and deionized water are then... Anhydrous ethanol and KH-540 were stirred at 640 rpm for 18 min until homogeneous. The mixture was then heated to 43℃ and stirred for 7 h. After centrifugation, the precipitate was washed four times each with anhydrous ethanol and deionized water, and dried at 48℃ to constant weight to obtain the negative ion release enhancement component. The mass ratio of modified electrical powder, chitosan aqueous solution, tetrabutyl titanate and mixture a was 1.5:50:3.4:22. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000 and anhydrous ethanol was 1:11:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol and KH-540 was 3:13:36:1.2.

[0022] Preparation Example 3 This preparation example provides a negative ion release enhancement component, which is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 9, stir at 550 rpm for 20 min until homogeneous, add dopamine, maintain the stirring speed, and continue stirring for 22 h. After filtration, wash 5 times with deionized water, and dry at 56 °C to constant weight to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.6:60:1.4. Step A2: Add the pretreated electrical powder, cerium nitrate, lanthanum nitrate, and zinc nitrate to deionized water. Control the ultrasonic frequency at 50 kHz and the ultrasonic power at 500 W, and ultrasonicate for 22 min until homogeneous. While stirring at 540 rpm, add 6 M ammonia water to adjust the pH to 9, stir for 35 min, filter, dry at 54 °C to constant weight, calcine at 460 °C for 28 min, and cool to room temperature to obtain modified electrical powder. The mass ratio of pretreated electrical powder, cerium nitrate, lanthanum nitrate, zinc nitrate, and deionized water is 5.5:0.85:0.8:0.5:40. Step A3: The modified electrical powder and a 3% (w / w) chitosan aqueous solution are stirred at 520 rpm for 24 min until homogeneous. The pH is adjusted to 2.2 with a 22% (w / w) acetic acid solution. Tetrabutyl titanate is then added, and a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol (a) is added dropwise over 10 min. After the addition is complete, the temperature is raised to 134℃, and the stirring speed is maintained. The reaction is continued for 28 h. The mixture is washed five times each with anhydrous ethanol and deionized water, dried at 64℃ to constant weight, and then calcined at 510℃ for 2.2 h to obtain functionalized core-shell particles. The functionalized core-shell particles and deionized water are then... Anhydrous ethanol and KH-550 were stirred at 660 rpm for 22 min until homogeneous. The mixture was then heated to 46℃ and stirred for 8 h. After centrifugation, the precipitate was washed 5 times each with anhydrous ethanol and deionized water, and dried at 50℃ to constant weight to obtain the negative ion release enhancement component. The mass ratio of modified electrical powder, chitosan aqueous solution, tetrabutyl titanate and mixture a was 1.6:60:3.6:24. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000 and anhydrous ethanol was 1:12:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol and KH-550 was 4:16:40:1.4.

[0023] Comparative Preparation Example 1 This comparative preparation example provides a negative ion release enhancement component, which is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 8, stir at 510 rpm for 12 min until homogeneous, add dopamine, maintain the stirring speed, and continue stirring for 18 h. Filter, wash three times with deionized water, and dry at 52 °C to constant weight to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.2:50:0.8. Step A2: Add the pretreated electrical powder, lanthanum nitrate, and zinc nitrate to deionized water, control the ultrasonic frequency at 40kHz and the ultrasonic power at 600W, and sonicate for 14 minutes until homogeneous. While stirring at 460rpm, add 4M ammonia water to adjust the pH to 8, stir for 25 minutes, filter, dry at 46℃ to constant weight, place at 430℃ for 24 minutes, cool to room temperature, and obtain modified electrical powder. The mass ratio of pretreated electrical powder, lanthanum nitrate, zinc nitrate, and deionized water is 4.5:0.6:0.4:20. Step A3: The modified electrical powder and a 1% (w / w) chitosan aqueous solution are stirred at 480 rpm for 16 min until homogeneous. The pH is adjusted to 2 with an 18% (w / w) acetic acid solution. Tetrabutyl titanate is then added, and a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol (a) is added dropwise over 10 min. After the addition is complete, the temperature is raised to 128℃, and the stirring speed is maintained. The reaction is continued for 24 h. The mixture is washed three times each with anhydrous ethanol and deionized water, dried at 56℃ to constant weight, and then calcined at 490℃ for 2 h to obtain functionalized core-shell particles. The functionalized core-shell particles, deionized water, and... Anhydrous ethanol and KH-550 were stirred at 620 rpm for 14 min until homogeneous. The mixture was then heated to 40 °C and stirred for 6 h. After centrifugation, the precipitate was washed three times each with anhydrous ethanol and deionized water, and dried at 46 °C to constant weight to obtain the negative ion release enhancement component. The mass ratio of modified electrical powder, chitosan aqueous solution, tetrabutyl titanate, and mixture a was 1.4:40:3.2:20. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol was 1:10:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol, and KH-550 was 2:10:32:1.

[0024] Comparative Preparation Example 2 This comparative preparation example provides a negative ion release enhancement component, which is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 8, stir at 510 rpm for 12 min until homogeneous, add dopamine, maintain the stirring speed, and continue stirring for 18 h. Filter, wash three times with deionized water, and dry at 52 °C to constant weight to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.2:50:0.8. Step A2: Add the pretreated electrical powder, cerium nitrate, and lanthanum nitrate to deionized water, control the ultrasonic frequency at 40kHz and the ultrasonic power at 600W, and sonicate for 14 minutes until homogeneous. While stirring at 460rpm, add 4M ammonia water to adjust the pH to 8, stir for 25 minutes, filter, dry at 46℃ to constant weight, place at 430℃ for 24 minutes, cool to room temperature, and obtain modified electrical powder. The mass ratio of pretreated electrical powder, cerium nitrate, lanthanum nitrate, and deionized water is 4.5:0.65:0.6:20. Step A3: The modified electrical powder and a 1% (w / w) chitosan aqueous solution are stirred at 480 rpm for 16 min until homogeneous. The pH is adjusted to 2 with an 18% (w / w) acetic acid solution. Tetrabutyl titanate is then added, and a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol (a) is added dropwise over 10 min. After the addition is complete, the temperature is raised to 128℃, and the stirring speed is maintained. The reaction is continued for 24 h. The mixture is washed three times each with anhydrous ethanol and deionized water, dried at 56℃ to constant weight, and then calcined at 490℃ for 2 h to obtain functionalized core-shell particles. The functionalized core-shell particles, deionized water, and... Anhydrous ethanol and KH-550 were stirred at 620 rpm for 14 min until homogeneous. The mixture was then heated to 40 °C and stirred for 6 h. After centrifugation, the precipitate was washed three times each with anhydrous ethanol and deionized water, and dried at 46 °C to constant weight to obtain the negative ion release enhancement component. The mass ratio of modified electrical powder, chitosan aqueous solution, tetrabutyl titanate, and mixture a was 1.4:40:3.2:20. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol 1000, and anhydrous ethanol was 1:10:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol, and KH-550 was 2:10:32:1.

[0025] Comparative preparation example 3 This comparative preparation example provides a negative ion release enhancement component, which is prepared by the following steps: Step A1: Add the electrical powder to a Tris-HCl buffer solution with a pH of 8, stir at 510 rpm for 12 min until homogeneous, add dopamine, maintain the stirring speed, and continue stirring for 18 h. Filter, wash three times with deionized water, and dry at 52 °C to constant weight to obtain pretreated electrical powder. The mass ratio of electrical powder, Tris-HCl buffer solution and dopamine is 1.2:50:0.8. Step A2: Add the pretreated electrical powder, cerium nitrate, lanthanum nitrate, and zinc nitrate to deionized water. Control the ultrasonic frequency at 40kHz and the ultrasonic power at 600W, and sonicate for 14 minutes until homogeneous. While stirring at 460rpm, add 4M ammonia water to adjust the pH to 8, stir for 25 minutes, filter, dry at 46℃ to constant weight, calcine at 430℃ for 24 minutes, and cool to room temperature to obtain modified electrical powder. The mass ratio of pretreated electrical powder, cerium nitrate, lanthanum nitrate, zinc nitrate, and deionized water is 4.5:0.65:0.6:0.4:20. Step A3: The modified electrical powder and a 1% (w / w) chitosan aqueous solution are stirred at 480 rpm for 16 min until homogeneous. The pH is adjusted to 2 with an 18% (w / w) acetic acid solution. Tetrabutyl titanate is then added, and a mixture of polyoxyethylene polyoxypropylene ether and anhydrous ethanol (a) is added dropwise over 10 min. After the addition is complete, the temperature is raised to 128℃, and the stirring speed is maintained. The reaction is continued for 24 h. The mixture is washed three times each with anhydrous ethanol and deionized water, dried at 56℃ to constant weight, and then calcined at 490℃ for 2 h to obtain functionalized core-shell particles. The functionalized core-shell particles and deionized water are then... Anhydrous ethanol and KH-550 were stirred at 620 rpm for 14 min until homogeneous. The mixture was then heated to 40℃ and stirred for 6 h. After centrifugation, the precipitate was washed three times each with anhydrous ethanol and deionized water, and dried at 46℃ to constant weight to obtain the negative ion release enhancement component. The mass ratio of modified electrical powder, chitosan aqueous solution, tetrabutyl titanate, and mixture a was 1.4:40:3.2:20. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether to anhydrous ethanol was 1:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol, and KH-550 was 2:10:32:1.

[0026] Preparation Examples 4-6 and Comparative Preparation Example 4 provide an aldehyde removal component.

[0027] Preparation Example 4 This preparation example provides a formaldehyde removal component, which is prepared by the following steps: Step B1: Mix sodium alginate and deionized water, stir at 510 rpm for 14 min at room temperature until homogeneous, adjust the pH to 10 with 0.006% sodium hydroxide aqueous solution, then add allyl glycidyl ether dropwise over 10 min, raise the temperature to 62℃, maintain the stirring speed, and continue stirring for 5.4 h, then adjust the pH to neutral with 0.01% hydrochloric acid aqueous solution, wash three times with deionized water, and dry at 56℃ to constant weight to obtain unsaturated sodium alginate, wherein the mass ratio of sodium alginate, deionized water and allyl glycidyl ether is 3.2:70:15; Step B2: Add hydroxypropyl acrylate and methacrylic acid to deionized water, control the stirring speed at 600 rpm, stir for 15 min until homogeneous, adjust the pH to 6 with 2% citric acid aqueous solution, raise the temperature to 56℃, stir and dropwise add a mixture b of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF, control the addition to be completed in 15 min, continue stirring and react for 1.2 h, wash 3 times with deionized water, dry at 62℃ to constant weight to obtain the aldehyde-removing component, wherein the mass ratio of hydroxypropyl acrylate, methacrylic acid, deionized water and mixture b is 1.2:40:20:0.06, and the mass ratio of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF in mixture b is 2.6:14:0.6:0.2:25.

[0028] Preparation Example 5 This preparation example provides a formaldehyde removal component, which is prepared by the following steps: Step B1: Mix sodium alginate and deionized water, stir at 530 rpm for 16 min at room temperature until homogeneous, adjust the pH to 10.5 with 0.0022% sodium hydroxide aqueous solution, then add allyl glycidyl ether dropwise over 10 min, raise the temperature to 67℃, maintain the stirring speed, and continue stirring for 5.8 h, then adjust the pH to neutral with 0.015% hydrochloric acid aqueous solution, wash 4 times with deionized water, and dry at 60℃ to constant weight to obtain unsaturated sodium alginate, wherein the mass ratio of sodium alginate, deionized water and allyl glycidyl ether is 3.8:75:15; Step B2: Add hydroxypropyl acrylate and methacrylic acid to deionized water, control the stirring speed at 640 rpm, stir for 18 min until homogeneous, adjust the pH to 6.3 with 3% citric acid aqueous solution, raise the temperature to 59℃, stir and dropwise add a mixture b of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF, control the addition to 15 min, continue stirring and react for 1.4 h, wash 4 times with deionized water, dry at 66℃ to constant weight to obtain the aldehyde-removing component, wherein the mass ratio of hydroxypropyl acrylate, methacrylic acid, deionized water and mixture b is 1.4:45:24:0.07, and the mass ratio of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF in mixture b is 2.9:16:0.7:0.3:25.

[0029] Preparation Example 6 This preparation example provides a formaldehyde removal component, which is prepared by the following steps: Step B1: Mix sodium alginate and deionized water, stir at 550 rpm for 18 minutes at room temperature until homogeneous, adjust the pH to 11 with 0.04% sodium hydroxide aqueous solution, then add allyl glycidyl ether dropwise over 10 minutes, raise the temperature to 70°C, continue stirring for 6.2 hours, adjust the pH to neutral with 0.02% hydrochloric acid aqueous solution, wash 5 times with deionized water, and dry at 64°C to constant weight to obtain unsaturated sodium alginate, wherein the mass ratio of sodium alginate, deionized water and allyl glycidyl ether is 4.4:80:15; Step B2: Add hydroxypropyl acrylate and methacrylic acid to deionized water, control the stirring speed at 680 rpm, stir for 21 min until homogeneous, adjust the pH to 6.6 with 4% citric acid aqueous solution, raise the temperature to 62℃, stir and dropwise add a mixture b of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF, control the addition to be completed in 15 min, maintain the stirring speed, continue stirring and react for 1.6 h, wash 5 times with deionized water, dry at 70℃ to constant weight, to obtain the aldehyde-removing component, wherein the mass ratio of hydroxypropyl acrylate, methacrylic acid, deionized water and mixture b is 1.6:50:28:0.08, and the mass ratio of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF in mixture b is 3.2:18:0.8:0.4:25.

[0030] Comparative preparation example 4 This comparative preparation example provides a formaldehyde removal component, which is prepared by the following steps: Step B1: Mix sodium alginate and deionized water, stir at 510 rpm for 14 min at room temperature until homogeneous, adjust the pH to 10 with 0.006% sodium hydroxide aqueous solution, then add isopropyl glycidyl ether dropwise over 10 min, raise the temperature to 62℃, maintain the stirring speed, and continue stirring for 5.4 h, then adjust the pH to neutral with 0.01% hydrochloric acid aqueous solution, wash three times with deionized water, and dry at 56℃ to constant weight to obtain unsaturated sodium alginate, wherein the mass ratio of sodium alginate, deionized water, and isopropyl glycidyl ether is 3.2:70:15; Step B2: Add hydroxypropyl acrylate and methacrylic acid to deionized water, control the stirring speed at 600 rpm, stir for 15 min until homogeneous, adjust the pH to 6 with 2% citric acid aqueous solution, raise the temperature to 56℃, stir and dropwise add a mixture b of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF, control the addition to be completed in 15 min, continue stirring and react for 1.2 h, wash 3 times with deionized water, dry at 62℃ to constant weight to obtain the aldehyde-removing component, wherein the mass ratio of hydroxypropyl acrylate, methacrylic acid, deionized water and mixture b is 1.2:40:20:0.06, and the mass ratio of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF in mixture b is 2.6:14:0.6:0.2:25.

[0031] Examples 1-3 and Comparative Examples 1-4 provide an automotive essence that removes formaldehyde and releases negative ions, and a method for preparing the same.

[0032] Example 1 This embodiment provides a car essence that removes formaldehyde and releases negative ions, comprising the following raw materials in parts by weight: 500 parts of deionized water, 18 parts of the negative ion release enhancement component prepared in Preparation Example 1, 12 parts of the aldehyde removal component prepared in Preparation Example 4, 30 parts of anhydrous ethanol, 8 parts of Orotan 731A, 14 parts of phenoxyethanol, 22 parts of initiator solution and 6 parts of citral. The preparation method of this car essence that removes formaldehyde and releases negative ions includes the following steps: The formaldehyde-removing component and anhydrous ethanol were added to deionized water, and the stirring speed was controlled at 840 rpm for 18 minutes until homogeneous. While maintaining the stirring speed, the negative ion release enhancement component, Orotan 731A, phenoxyethanol and initiator solution were added. The temperature was raised to 76℃ and stirring was continued for 2 hours. After cooling to room temperature, citral was added, and the stirring speed was controlled at 660 rpm for 12 minutes until homogeneous, thus obtaining a car essence that removes formaldehyde and releases negative ions. The initiator solution was a 12% ammonium persulfate aqueous solution.

[0033] Example 2 This embodiment provides a car essence that removes formaldehyde and releases negative ions, comprising the following raw materials in parts by weight: 550 parts of deionized water, 21 parts of the negative ion release enhancement component prepared in Preparation Example 2, 16 parts of the formaldehyde removal component prepared in Preparation Example 5, 35 parts of anhydrous ethanol, 11 parts of BYK-190, 16 parts of phenoxyethanol, 24 parts of initiator solution, and 8 parts of citral. The preparation method of this car essence that removes formaldehyde and releases negative ions includes the following steps: Add the formaldehyde removal component and anhydrous ethanol to deionized water, control the speed at 880 rpm, stir for 22 minutes until uniform, maintain the speed, and add the negative ion release enhancement component, BYK-190, phenoxyethanol and initiator solution while stirring, heat to 78℃, continue stirring for 3 hours, cool to room temperature, then add citral, control the speed at 680 rpm, stir for 16 minutes until uniform, and obtain the car essence initiator solution with a mass fraction of 14% ammonium persulfate aqueous solution that removes formaldehyde and releases negative ions.

[0034] Example 3 This embodiment provides a car essence that removes formaldehyde and releases negative ions, comprising the following raw materials in parts by weight: 600 parts of deionized water, 24 parts of the negative ion release enhancement component prepared in Preparation Example 3, 20 parts of the aldehyde removal component prepared in Preparation Example 6, 40 parts of anhydrous ethanol, 14 parts of Orotan 731A, 18 parts of phenoxyethanol, 26 parts of initiator solution and 10 parts of citral. The preparation method of this car essence that removes formaldehyde and releases negative ions includes the following steps: The formaldehyde-removing component and anhydrous ethanol were added to deionized water, and the mixture was stirred at 920 rpm for 26 minutes until homogeneous. While maintaining the stirring speed, the negative ion release enhancement component, Orotan 731A, phenoxyethanol, and initiator solution were added. The mixture was heated to 80°C and stirred for 4 hours. After cooling to room temperature, citral was added, and the mixture was stirred at 700 rpm for 20 minutes until homogeneous. This yielded a car essence that removes formaldehyde and releases negative ions. The initiator solution was a 16% (w / w) ammonium persulfate aqueous solution. Comparative Example 1 Comparative Example 1 is the same as Example 1, except that the negative ion release enhancement component in Example 1 is replaced with the negative ion release enhancement component prepared in Comparative Preparation Example 1.

[0035] Comparative Example 2 Comparative Example 2 is the same as Example 1, except that the negative ion release enhancement component in Example 1 is replaced with the negative ion release enhancement component prepared in Comparative Preparation Example 2.

[0036] Comparative Example 3 Comparative Example 3 is the same as Example 1, except that the negative ion release enhancement component in Example 1 is replaced with the negative ion release enhancement component prepared in Comparative Preparation Example 3.

[0037] Comparative Example 4 Comparative Example 4 is the same as Example 1, except that the formaldehyde removal component in Example 1 is replaced with the formaldehyde removal component prepared in Comparative Preparation Example 4.

[0038] Performance testing Formaldehyde gas adsorption test: The elimination of free formaldehyde in engineered wood products is used as the evaluation index for formaldehyde removal rate.

[0039] Eight pieces with an area of ​​1m 2 The formaldehyde release is 5.0 mg / m³. 3 Medium-density fiberboard (MDF) was placed into eight formaldehyde emission testing climate chambers. Three of these chambers contained the automotive essence prepared in Examples 1-3, four contained the automotive essence prepared in Comparative Examples 1-4 (as the experimental group), and the remaining chamber served as a blank control. After 72 hours, the formaldehyde concentration in each chamber was measured, and the formaldehyde removal rate of different adsorption particles was calculated using the following formula: Formaldehyde removal rate (%) = (Concentration of blank control - Concentration of experimental group) / Concentration of blank control; Negative ion release test: The car essences in Examples 1-3 and Comparative Examples 1-4 were uniformly coated on polytetrafluoroethylene plates, with the coating thickness controlled at 50 μm. The plates were cut into 16 cm × 16 cm sizes and placed at room temperature of 24 ± 2 °C and humidity of 70 ± 2% for 12 h. The negative ion release was measured using an ion meter. Antibacterial performance test: The automotive essences from Examples 1-3 and Comparative Examples 1-4 were used to test the antibacterial performance and antibacterial durability of the antibacterial coatings according to the test methods in GB / T 21866-2008 "Determination of Antibacterial Properties and Antibacterial Effects of Antibacterial Coatings (Films)". Taking the inhibition effect of Escherichia coli and Candida albicans as an example, the average antibacterial rate of Escherichia coli and Candida albicans was calculated. The test results are shown in Table 1. Table 1 Performance Tests of Car Essence As shown in Table 1, compared with Comparative Examples 1-4, the automotive essence prepared in this application has superior formaldehyde removal ability, negative ion release ability and antibacterial effect.

[0040] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A car essence that removes formaldehyde and releases negative ions, characterized in that, Including the following parts by weight of raw materials: 500-600 parts deionized water, 18-24 parts negative ion release enhancement component, 12-20 parts formaldehyde removal component, 30-40 parts anhydrous ethanol, 8-14 parts dispersant, 14-18 parts phenoxyethanol, 22-26 parts initiator solution, and 6-10 parts citral; The negative ion release enhancement component is first obtained by self-polymerization of electrical powder and dopamine to obtain pretreated electrical powder, then calcined with cerium nitrate, lanthanum nitrate and zinc nitrate to obtain modified electrical powder, then obtained by sol-gel method with tetrabutyl titanate to obtain functionalized core-shell particles, and finally modified with silane coupling agent to obtain the final product. The formaldehyde removal component is prepared by ring-opening esterification of sodium alginate and allyl glycidyl ether to obtain unsaturated sodium alginate, which is then chemically crosslinked with hydroxypropyl acrylate and methacrylic acid. The dispersant is Orotan 731A or BYK-190; The initiator solution is an aqueous solution of ammonium persulfate with a mass fraction of 12-16%; The silane coupling agent is KH-550 or KH-540.

2. The car essence that removes formaldehyde and releases negative ions according to claim 1, characterized in that, The negative ion release-enhancing component is prepared by the following steps: Step A1: Add the electrical powder to Tris-HCl buffer solution, stir until homogeneous, add dopamine, stir and react for 18-22 hours, filter, wash and dry to obtain pretreated electrical powder; Step A2: Add the pretreated electrical powder, cerium nitrate, lanthanum nitrate and zinc nitrate to deionized water, ultrasonically disperse evenly, adjust the pH to 8-9, stir for 25-35 min, filter, dry, place at 430-460℃, calcine for 24-28 min, cool to room temperature, and obtain modified electrical powder; Step A3: Mix the modified electrical powder and crosslinking agent evenly, adjust the pH to 2-2.2, add tetrabutyl titanate, stir and dropwise add a mixture of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol and anhydrous ethanol, controlling the dropwise addition to be completed within 10 minutes. After the dropwise addition is completed, raise the temperature to 128-134℃, continue stirring and reacting for 24-28 hours, wash, dry, and then calcine at 490-510℃ for 2-2.2 hours to obtain functionalized core-shell particles. Mix the functionalized core-shell particles, deionized water, anhydrous ethanol and silane coupling agent evenly, raise the temperature to 40-46℃, stir and react for 6-8 hours, centrifuge, precipitate, wash and dry to obtain the negative ion release enhancement component. In step A3, the crosslinking agent is a chitosan aqueous solution with a mass fraction of 1-3%.

3. The car essence for removing formaldehyde and releasing negative ions according to claim 2, characterized in that, In step A1, the mass ratio of electrical powder, Tris-HCl buffer, and dopamine is 1.2-1.6: 50-60: 0.8-1.

4.

4. The car essence for removing formaldehyde and releasing negative ions according to claim 2, characterized in that, In step A2, the mass ratio of pretreated electrical powder, cerium nitrate, lanthanum nitrate, zinc nitrate, and deionized water is 4.5-5.5: 0.65-0.85: 0.6-0.8: 0.4-0.5: 20-40.

5. The car essence for removing formaldehyde and releasing negative ions according to claim 2, characterized in that, In step A3, the mass ratio of modified electrical powder, crosslinking agent, tetrabutyl titanate, and mixture a is 1.4-1.6:40-60:3.2-3.6:20-24. In mixture a, the mass ratio of polyoxyethylene polyoxypropylene ether, polyvinyl alcohol, and anhydrous ethanol is 1:10-12:20, and the mass ratio of functionalized core-shell particles, deionized water, anhydrous ethanol, and silane coupling agent is 2-4:10-16:32-40:1-1.

4.

6. The car essence for removing formaldehyde and releasing negative ions according to claim 1, characterized in that, The formaldehyde-removing component is prepared by the following steps: Step B1: Mix sodium alginate and deionized water, stir evenly at room temperature, adjust the pH to 10-11, then add allyl glycidyl ether dropwise, controlling the addition to be completed within 10 minutes, raise the temperature to 64-70℃, continue stirring for 5.4-6.2 hours, then adjust the pH to neutral, wash, and dry to obtain unsaturated sodium alginate. Step B2: Add hydroxypropyl acrylate and methacrylic acid to deionized water, mix well, adjust the pH to 6-6.6, heat to 56-62℃, stir and dropwise add a mixture of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether and anhydrous THF, controlling the dropwise addition to be completed in 15 minutes, continue stirring and reacting for 1.2-1.6 hours, wash, dry, and obtain the aldehyde-removing component.

7. The car essence for removing formaldehyde and releasing negative ions according to claim 6, characterized in that, In step B1, the mass ratio of sodium alginate, deionized water, and allyl glycidyl ether is 3.2-4.4:70-80:

15.

8. The car essence for removing formaldehyde and releasing negative ions according to claim 6, characterized in that, In step B2, the mass ratio of hydroxypropyl acrylate, methacrylic acid, deionized water and mixture b is 1.2-1.6:40-50:20-28:0.06-0.

08.

9. A car essence for removing formaldehyde and releasing negative ions according to claim 6, characterized in that, In the mixture b, the mass ratio of unsaturated sodium alginate, saturated calcium chloride aqueous solution, activated carbon, glycerol triglycidyl ether, and anhydrous THF is 2.6-3.2:14-18:0.6-0.8:0.2-0.4:

25.

10. A method for preparing an automotive essence that removes formaldehyde and releases negative ions as described in any one of claims 1-9, characterized in that, Includes the following steps: Add the formaldehyde-removing component and anhydrous ethanol to deionized water and stir until homogeneous. While stirring, add the negative ion release enhancement component, dispersant, phenoxyethanol and initiator solution, heat to 76-80℃, continue stirring for 2-4 hours, cool to room temperature, then add citral and stir until homogeneous to obtain a car essence that removes formaldehyde and releases negative ions.

Citation Information

Patent Citations

  • Modified tourmaline powder for ceramic glaze, anion ceramic glaze and preparation method

    CN105541410A

  • Organic-inorganic composite formaldehyde catalytic composition, preparation method and air purification filter element

    CN112058308A

  • Automobile essence capable of removing formaldehyde and releasing negative ions, and preparation method thereof

    CN112121612A

  • Air purification ceramic material and preparation method thereof

    CN115925393A

  • Porous spraying core configured to release negative ions, and method for production thereof

    RU2825752C1

Cited By

  • Nanometer type multifunctional negative ion material and preparation method thereof

    CN121488974A